Pelatihan Art-Enginering Untuk Meningkatkan Keterampilan Pemuda Karang Taruna Griya Asri Kalitengah - Metatia Intan Mauliana (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2019)
Karang Taruna is a social forum that is expected to be able to overcome various social problems that produce young generations and are able to develop the potential of the younger generation in their environment in the frame of increasing the level of social welfare of the community. This great mission from Karang Taruna cannot always be smooth, for example in the Griya Asri Karang Taruna Group. Griya Asri Kalitengah Karang Taruna is a Taruna reef that is quite active in the social field, but this group has a positive foundation that can hone skills and can increase motivation to be a creative and independent generation. Therefore, the researchers took the initiative to conduct an Art-Enginering (Areng) training on Pemuda Karang Taruna Griya Asri Kalitengah with Pawitra Ruang Seni to improve their skills in art and the manufacture of simple tools. Components of Training Success are viewed from the achievement of the target number of trainees and the achievement of training objectives. At the level of achievement of the target number of trainees from the data of members of the Asri Kalitengah Griya Karang Taruna can determine the target participants get 50% of the total member data and 77% of the total active members. As for the target achievement of goals in terms of changes in perceptions and motivations improved by using the questionnaire and questionnaire methods, while the assessment of changes in skills was reviewed from the implementation of the program agenda before and after the participants attended the training. In addition, it was also reviewed from the first activities carried out by cadets at regular meetings after the training was held. The general results of the data obtained from the training are good. From what is seen from the motivation, the quality of the practices that have been produced by the participants, it can be concluded that the objectives of this activity have been obtained.